2010
DOI: 10.1161/atvbaha.109.200949
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Enhances Angiogenesis and Arteriogenesis by Modulating Smooth Muscle Cell and Macrophage Function

Abstract: Objective-In a previous study we identified metallothionein (MT) as a candidate gene potentially influencing collaterogenesis. In this investigation, we determined the effect of MT on collaterogenesis and examined the mechanisms contributing to the effects we found. Methods and Results-Collateral blood flow recovery was assessed using laser Doppler perfusion imaging, and angiogenesis was measured using a Matrigel plug assay. Smooth muscle cells were isolated from MT knockout (KO) mice for functional assays. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…As a result, effective angiogenesis in vivo following MT-I knockdown is hampered. This was confirmed by Zbinden et al [9], who found decreased vessel density and less EC migration in matrigel plugs implanted in MTI/II knockout mice as compared to wild-type animals. …”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…As a result, effective angiogenesis in vivo following MT-I knockdown is hampered. This was confirmed by Zbinden et al [9], who found decreased vessel density and less EC migration in matrigel plugs implanted in MTI/II knockout mice as compared to wild-type animals. …”
Section: Introductionsupporting
confidence: 63%
“…At the same time, MTs have been shown to be involved in neovessel formation, i.e. angiogenesis, both in vitro and in vivo [8,9]. By inducing angiogenesis, MTs could provide a possible feedback mechanism to counteract oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide transcriptome analysis of satellite cells overexpressing Bmi1 revealed significantly increased expression of MT1, which has been shown to be necessary to maintain proliferation and normal cellular functions under stress conditions, including when cells reenter the cell cycle from a quiescent state (Zbinden et al, 2010). In keeping with this notion, improvement of muscle strength is seen only in those mdx mice in which up-regulation of MT1 occurred concomitantly with overexpression of Bmi1 in satellite cells.…”
Section: Bmi1 Expression Is Reduced In Patients Affected By Dmdmentioning
confidence: 86%
“…Indeed, there was a Ͼ600-fold increase in MT3 mRNA level, although such an apparently large response reflects, to some extent, the fact that expression is minimal in adipocytes incubated under normoxic conditions (208). The metallothioneins are low molecular weight (ϳ6,000 M r ) cysteine-rich, metal-binding proteins, with several presumed functions which include angiogenesis and antioxidant defense (129,150,230). A proangiogenic role in adipose tissue would be consistent with the major induction of MT3 expression by hypoxia.…”
Section: Hypoxia and Global Gene Expressionmentioning
confidence: 99%